How turbidity current frequency and character varies down a fjord‐delta system: Combining direct monitoring, deposits and seismic data. Issue 1 (29th January 2019) - Stacey, Cooper D.; Hill, Philip R.; Talling, Peter J.; Enkin, Randolph J.; Hughes Clarke, John; Lintern, D. Gwyn
Abstract: Submarine turbidity currents are one of the most important processes for moving sediment across our planet; they are hazardous to offshore infrastructure, deposit petroleum reservoirs worldwide, and may record tsunamigenic landslides. However, there are few studies that have monitored these submarine flows in action, and even fewer studies that have combined direct monitoring with longer‐term records from core and seismic data of deposits. This article provides one of the most complete studies yet of a turbidity current system. The aim here is to understand what controls changes in flow frequency and character along the turbidite system. The study area is a 12 km long delta‐fed fjord (Howe Sound) in British Columbia, Canada. Over 100 often powerful (up to 2 to 3 m sec −1 ) events occur each year in the highly‐active proximal channels, which extend for 1 to 2 km from the delta lip. About half of these events reach the lobes at the channel mouths. However, flow frequency decreases rapidly once these initially sand‐rich flows become unconfined, and only one to five flows run out across the mid‐slope each year. Many of these sand‐rich, channelized, delta‐sourced flows therefore dissipated over a few hundred metres, once unconfined, rather than eroding and igniting. Upflow migrating bedforms indicate that supercritical flow dominated in the proximal channels and lobes, and also across the unconfined mid‐slope. These supercritical flows deposited thick sand beds in proximal channels and lobes, but thinner and finer beds on the unconfined mid‐slope. The distal flat basin records far larger volume and more hazardous events that have a recurrence interval of ca 100 years. This study shows how sand‐rich delta‐fed flows dissipate rapidly once they become unconfined, that supercritical flows dominate in both confined and unconfined settings, and how a second type of more hazardous, and much less frequent event is linked to a different scale of margin failure.